The body's perilous pleasures : dangerous desires and contemporary culture - Aaron, Michele (Edinburgh University Press, 1999)
Drawing upon contemporary film and fiction, The Body's Perilous Pleasures is an investigation of the nature of the body and the manner in which it figures in transvestism, cyborgs and female desire, body piercing, AIDS and reincarnation.